Determining the productivity of modern forestry machines in various conditions - Svoikin F.V.; Rossikhin K.V.; Taraban M.V.; Kalyashov V.A.; Bozhbov V.E.; Borozna A.A.; Pomortseva A.E.; Kambarov A.A. (BIO Web of Conferences)
Real data on the production of the timber industry cluster of the Russian Federation in 2023-2024 are indicated, an overview of trends in the logging industry of the Russian Federation is given in the conditions of the new economic reality: digitalization, digitalization. import substitution, changes in sales markets for logging and wood processing products. Experimental data on the operation of a wheeled log picker based on the TROM snow and swamp-going equipment in the conditions of development of hard-to-reach logging sites according to the following options are presented: the Komi Republic and the Khanty-Mansi Autonomous Okrug Yugra. The performance of the machine under various operating conditions was determined. Calculation diagrams of technological processes in which this technology can exist have been compiled and given.